From dysmotility to virulent pathogens: implications of opioid use in the ICU. Issue 2 (April 2018) - Chapple, Lee-anne; Deane, Adam
Abstract : Purpose of review: Gastrointestinal dysmotility occurs frequently in the critically ill. Although the causes underlying dysmotility are multifactorial, both pain and its treatment with exogenous opioids are likely causative factors. The purpose of this review is to describe the effects of pain and opioids on gastrointestinal motility; outline the rationale for and evidence supporting the administration of opioid antagonists to improve dysmotility; and describe the potential influence opioids drugs have on the intestinal microbiome and infectious complications. Recent findings: Opioid drugs are frequently prescribed in the critically ill to alleviate pain. In health, opioids cause gastric dysmotility, yet the evidence for this in critical illness is inconsistent and limited to observational studies. Administration of opioid antagonists may improve gastrointestinal motility, but data are sparse, and these agents cannot be recommended outside of clinical trials. Although critical illness is associated with alterations in the microbiome, the extent to which opioid administration influences these changes, and the subsequent development of infection, remains uncertain. Summary: Replication of clinical studies from ambulant populations in critical care is required to ascertain the independent influence of opioid administration on gastrointestinal motility and infectious complications.